Amendment of Higher Education Institution Quality Assurance System Activities - Jakhongir Shaturaev (Universitas Pendidikan Indonesia (UPI), 2023)
The work aims to improve the system for assessing the quality of activities of higher education institutions in terms of quality management. Problems that hinder the improvement of the quality of universities' activities are identified and systematized. An analysis of the existing criteria-evaluation complexes used to determine the effectiveness of the activities of higher education institutions was carried out. The content of the components of the quality of the activities of higher education institutions has been clarified. A structural model for assessing the internal quality of higher education institutions is proposed. The analysis of the macro-environment of the activity of the university was carried out using the methodology of strategic management, including political, economic, social, and technological (PEST) analysis. The result of the study is a macro-criteria model of the quality management system of higher education institutions, which characterizes quality management, a new approach to assessing the effectiveness of a university and the degree of its competitiveness, as well as the activities of higher education institutions in terms of quality management.